Enhancing Strawberry Harvesting Efficiency through Yolo-v7 Object Detection Assessment - Nergiz, Mehmet (Fırat Üniversitesi, 2023)
Strawberry fruits which are rich in vitamin A and carotenoids offer benefits for maintaining healthy epithelial tissues and promoting maturity and growth. The intensive cultivation and swift maturation of strawberries make them susceptible to premature harvesting, leading to spoilage and financial losses for farmers. This underscores the need for an automated detection method to monitor strawberry development and accurately identify growth phases of fruits. To address this challenge, a dataset called Strawberry-DS, comprising 247 images captured in a greenhouse at the Agricultural Research Center in Giza, Egypt, is utilized in this research. The images of the dataset encompass various viewpoints, including top and angled perspectives, and illustrate six distinct growth phases: "green", “red”, "white", "turning", "early-turning" and "late-turning". This study employs the Yolo-v7 approach for object detection, enabling the recognition and classification of strawberries in different growth phases. The achieved mAP@.5 values for the growth phases are as follows: 0.37 for "green," 0.335 for "white," 0.505 for "early-turning," 1.0 for "turning," 0.337 for "late-turning," and 0.804 for "red". The comprehensive performance outcomes across all classes are as follows: precision at 0.792, recall at 0.575, mAP@.5 at 0.558, and mAP@.5:.95 at 0.46. Notably, these results show the efficacy of the proposed research, both in terms of performance evaluation and visual assessment, even when dealing with distracting scenarios involving imbalanced label distributions and unclear labeling of developmental phases of the fruits. This research article yields advantages such as achieving reasonable and reliable identification of strawberries, even when operating in real-time scenarios which also leads to a decrease in expenses associated with human labor.

A vitamini ve karotenoidler açısından zengin olan çilek meyveleri, sağlıklı epitel dokularını korur ve büyümeyi destekleyici faydalar sunar. Çileklerin yoğun ekimi ve hızlı olgunlaşması, bu meyveyi erken hasada duyarlı hale getirerek, çiftçiler için çürük hasat elde etmeye ve mali kayıplara yol açar. Bu durum, çilek gelişimini izlemek ve meyvelerin büyüme aşamalarını doğru bir şekilde belirlemek için otomatik bir algılama yöntemine olan ihtiyacı arttırmaktadır. Bu zorluğun üstesinden gelmek için, bu araştırmada Mısır'ın Giza kentindeki Tarımsal Araştırma Merkezi'ndeki bir serada çekilen 247 görüntüden oluşan Strawberry-DS adlı bir veri seti kullanılmıştır. Veri kümesinin görüntüleri, üstten ve açılı perspektifler dâhil olmak üzere çeşitli bakış açılarını kapsayacak şekilde altı farklı büyüme aşamasını içermektedir: "yeşil", "kırmızı", "beyaz", "dönüşüm", "erken-dönüşüm" ve "geç-dönüşüm". Bu çalışma, farklı büyüme evrelerindeki çileklerin tanınmasını ve sınıflandırılmasını tespit etmek için Yolo-v7 nesne tespiti yöntemini kullanmaktadır. Büyüme aşamaları için elde edilen mAP@.5 değerleri şu şekildedir: "yeşil" için 0,37, "beyaz" için 0,335, "erken-dönüşüm" için 0,505, "dönüşüm" için 1,0, "geç-dönüşüm" için 0,337 ve "kırmızı" için 0,804. Tüm sınıflardaki kapsamlı performans sonuçları ise şu şekildedir: 0,792'de kesinlik, 0,575'te hatırlama, 0,558'de mAP@.5 ve 0,46'da mAP@.5:.95. Özellikle, bu sonuçlar, dengesiz etiket dağılımları ve meyvelerin gelişim evrelerinin etiketlerinin net olmaması gibi etiketleri de içeren bir veri seti ile eğitilip test edilmesine rağmen, hem performans değerlendirmesi hem de görsel değerlendirme açısından önerilen araştırmanın etkinliğini göstermektedir. Bu araştırma makalesi, gerçek zamanlı senaryolarda çalışırken bile çileklerin makul ve güvenilir bir şekilde tespit edilmesi gibi avantajlar sağlamakta ve bu da işçilik maliyetlerinde azalmayı sağlamaktadır.
Yolo-v7 Nesne Tespiti ile Çilek Hasat Verimliliğinin Artırılması
Keywords: Image Processing; Görüntü İşleme; Machine Vision; Yapay Görme